Sex Dimorphic Associations of Gestational Diabetes Mellitus With Cord Plasma Fatty Acid Binding Protein 4 and Estradiol - Liu, Xin; Zheng, Tao; Xu, Ya-Jie; Yang, Meng-Nan; Wang, Wen-Juan; Huang, Rong; Zhang, Guang-Hui; Guo, Yu-Na; Zhang, Jun; Ouyang, Fengxiu; Li, Fei; Luo, Zhong-Cheng (Frontiers in Endocrinology, 2021)
Fatty acid binding protein 4 (FABP4) has been associated with insulin resistance. Gestational diabetes mellitus (GDM) impairs fetal insulin sensitivity. Female newborns are more insulin resistant than male newborns. We sought to evaluate the association between GDM and cord blood FABP4, and explore potential sex dimorphic associations and the roles of sex hormones. This was a nested case-control study in the Shanghai Birth Cohort, including 153 pairs of newborns in GDM vs. euglycemic pregnancies matched by infant sex and gestational age at delivery. Cord plasma FABP4, leptin, total and high-molecular-weight adiponectin, testosterone and estradiol concentrations were measured. Adjusting for maternal and neonatal characteristics, cord plasma FABP4 (Mean±SD: 27.0±19.6 vs. 18.8±9.6 ng/mL, P=0.045) and estradiol (52.0±28.6 vs. 44.2±26.6, ng/mL, P=0.005) concentrations were higher comparing GDM vs. euglycemic pregnancies in males, but similar in females (all P>0.5). Mediation analyses showed that the positive association between GDM and cord plasma FABP4 in males could be partly mediated by estradiol (P=0.03), but not by testosterone (P=0.72). Cord plasma FABP4 was positively correlated with total adiponectin in females (r=0.17, P=0.053), but the correlation was in the opposite direction in males (r=-0.11, P=0.16) (test for difference in r, P=0.02). Cord plasma FABP4 was not correlated with leptin in both sexes. The study is the first to demonstrate sex-dimorphic associations between GDM and cord plasma FABP4 or estradiol, and between FABP4 and adiponectin in newborns. GDM may affect fetal circulating FABP4 and estradiol levels in males only.